Literasi Perlindungan Konsumen pada Layanan Perbankan Syariah di Kalangan Mahasiswa Universitas Muara Bungo - Yudhi Novriansyah; Herawati Herawati; Usdeldi Usdeldi (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2026)
The development of Islamic banking activities in Indonesia currently is not matched by adequate understanding among students, particularly regarding the rights and obligations of customers, Sharia contract literacy, and consumer protection mechanisms. This Community Service Activity aims to enhance the understanding of Muara Bungo University students regarding customer rights and obligations, complaint procedures, basic sharia contract literacy, prevention of detrimental service practices, and the resolution process for sharia banking consumer disputes. The activity was attended by 50 students from all faculties and department, conducted using the Participatory Action Research (PAR) approach through the stages of problem identification, planning, implementation with interactive lecture methods, and evaluation. The results of the activity showed a significant increase in understanding, marked by the growing awareness of participants regarding the rights and obligations of customers, understanding of Islamic banking contracts, as well as the ability to comprehend consumer protection concepts and the dispute resolution process effectively. Consumer protection literacy education has proven to have a positive impact on students in preparing themselves to face the banking world, both in the context of employment and business in the future.